Beccadelli und der Schatz des Blinden. Der Weg einer Fabel von Lullus zu La Fontaine - Tschögele, Thomas (Wiener Studien, 2015)
Introduced into European literature by Ramon Llull around 1290, the fable known as The Blind Man's Treasure' was passed on and modified by various other authors before finding its way into La Fontaine's Fables. This article is concerned with the important role Antonio Beccadelli of Palermo (1394 - 1471) played in the process. It will be shown that Beccadelli drew from Llull's original fable, ignoring 14th-century adaptations, and that it was his version that was adapted by La Fontaine's source, Abstemius.